Midline incisional hernia prophylaxis using synthetic mesh in an emergency or urgent gastrointestinal tract surgery: a protocol for multicentre randomised clinical trial - Gareth Mckay; Ammarin Thakkinstian; John Attia; Suphakarn Techapongsatorn; Amarit Tansawet; Pawin Numthavaj; Preeda Sumritpradit (BMJ Open)
Introduction Between 5% and 30% of abdominal incisions eventually result in incisional hernias (IHs) that can lead to severe complications and impaired quality of life. Unfortunately, IH repair is often unsuccessful; therefore, hernia prophylaxis is an important issue. The efficacy of mesh augmentation has been proven for hernia prophylaxis in high-risk patients, but no randomised clinical trial has evaluated prophylactic mesh placement in emergency/urgent gastrointestinal operations.Methods and analysis A multicentre, prospective randomised, open and patient–assessor blinded endpoint design will be conducted. A total of 470 patients will be enrolled and randomly allocated to retrorectus mesh augmentation with lightweight polypropylene mesh or primary suture closure. The primary outcome is IH occurrence within 24 months of follow-up, while other clinical outcomes are secondary endpoints. A cost-effectiveness analysis will be conducted from the societal and provider perspectives.Ethics and dissemination Ethics approval was obtained from Ramathibodi Hospital (MURA2020/1478) and Vajira Hospital (COA164/2563). The protocol is on the process of submission to the local ethics committee of the other study sites. Results will be submitted for publication in a peer-reviewed journal.Trial registration number TCTR20200924002.